L’écologie industrielle : quand l’écosystème industriel devient un vecteur du développement durable - Arnaud Diemer; Sylvère Labrune (Développement Durable et Territoires, 2007)
Industrial ecology is defined by Robert Frosch (1995) as practices intended to reduce industrial pollution. That leads us to think industrial ecosystem as a vector of sustainable development.Ecological engineering and ecotechnology recommend managers to rationalize the production process (optimization of material consumptions, minimization of bads…). Industrial symbiosis and industrial parks are generally presented as models of industrial rationalization and tangible illustrations of the sustainable development.